STUDIES ON THE NONLINEAR INTERACTIONS ASSOCIATED WITH MOORED SEMI SUBMERSIBLE OFFSHORE PLATFORMS - NOUR ELFADUL ABBAS, YASSIR MOHAMMEDNOUR ELFADUL ABBAS (2011)
The design of moored semi submersible systems constitutes a challenging engineering problem in which, the platform offset, stability, payload and system-optimized cost requirements are to be met simultaneously. This problem is complicated by the incomplete understanding of the nonlinearities associated with the multiple interactions such as wave to wave, wave to platform, platform to mooring, fluid to mooring and mooring to seabed. In this study, an attempt has been made to probe into these nonlinearities through numerical, experimental, and parametric studies. In the numerical study, moored semi submersibles were analyzed in the time domain. The dynamic equilibrium conditions were satisfied through a set of coupled nonlinear differential equations for the six DOF motions. For representing the platform to mooring nonlinear interactions, the 6x6 mooring stiffness matrix was derived based on the mooring stiffness and on the fairlead coordinates relative to the structure CG. For the evaluation of the slow frequency horizontal motions of the platform, the second order wave forces resulting from the second order temporal acceleration and the structural first order motions were formulated. For the assessment of the fluid to mooring and mooring to seabed nonlinear interactions, a deterministic approach for the dynamic analysis of a multi-component mooring line was formulated. The floater motion responses were considered as the mooring line upper boundary conditions. Lumped parameter approach was adopted for the mooring line modeling. Mooring to seabed nonlinear interactions were modeled assuming that the mooring line rested on an elastic dissipative foundation. A numerical dynamic analysis method in the time domain was developed and results for various mooring lines partially lying on different soils were validated by conducting a comparative study against published results. The contribution of the soil characteristics of the seabed to the dynamic behavior of mooring line was investigated for different types of soil. Two phases of experimental studies were conducted to provide benchmark data for validating the numerical methods. In the first phase, the seakeeping performance of a semi submersible with eight circular columns was studied. The model was built to scale of 1:100 using Froud’s law of similitude. The tests were conducted for head, beam and quartering seas. In the second phase, a semi submersible with six circular columns was modeled using the same scale as for the first semi submersible. Linear mass-spring system was arranged to facilitate measurements of the horizontal drift forces. The system natural periods, still water damping, nonlinear viscous damping, drag coefficient and inertia coefficient information were evaluated from the free decay tests. Seakeeping tests were conducted for head and beam model orientations. The measured drift forces were compared to available formulae in the literature to assess the available semi-empirical methods for evaluation these forces. In both experimental phases, twin-hulled conventional semi submersibles were considered. By comparing the results of the numerical and experimental models, the validity of the numerical method was established. Based on the validated numerical algorithm, a number of parametric studies were conducted for investigating the contributions of various design parameters on the dynamics of moored semi submersibles. The effects of pretension, mooring line configuration, clump weight, cable unit weight, elongation, breaking strength and pretension angle on the behavior of multi-component mooring line, were investigated by using an implicit iterative solution of the catenary equations. On the other hand, using linearized frequency domain analysis, the contributions of platform payload, platform dimensions, number of columns, number of mooring lines, the wave environment mathematical model, the wave characteristics and the operating (intact or damage) conditions to the responses of moored semi submersibles were investigated. The experimental and published results verified the efficiency of the developed numerical model for prediction of the wave frequency and low frequency motions and mooring dynamic tension responses of the semi submersible. Moreover, experimental results indicated that in addition to the modeling of the mooring system stiffness, typical or hybrid modeling of the mooring system and attachments are necessary for the critical assessment of the mooring system damaged conditions.